Meniti Teks Ajaran Hindu sebagai Inspirasi Mewujudkan Profesionalitas Kerja sesuai Guna dan Karma - I Gusti Komang Kembarawan (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2021)
This study aims to conduct a study of Hindu literary texts that contain teachings about inspiration to realize work professionalism using the basis of guna and karma. The Hindu religious texts used as research data sources are the text of Agastya Parwa, the Vedic scriptures, and the Bhagavadgita. The text that is used as the source of research data is limited to aspects that contain aspects of the division of labor according to guna and karma. This study uses a qualitative descriptive method to analyze Hindu religious texts according to the research focus. More specifically, this study applies content analysis in order to find answers to the formulation of the problem posed. Based on the results of this study, two findings were found. First, the teachings that contain inspiration for work professionalism in Agastya Parwa's text are presented in the form of a dialogue which essentially states that work professionalism is inspired by grouping people based on chess colors. Second, the inspiration in building work professionalism contained in the teachings of the Agastya Parwa text is in harmony with the teachings of the Vedas and the Bhagavadgita, especially in determining professionalism based on guna and karma.